Vickery's law and accounts of executors, administrators and trustees - Kimmer, John.; Scriven, Graham; Stanfield, Russell (London : Cassell Education, 1987)
The aim of the authors is to have in one volume, an up-to-date, comprehensive and lucid coverage of the specialized and often complicated laws and practices relevant to the administration of those studying for various professional examinations, as well as being a standard reference book for practitioners in the legal and accountancy professions.
Includes index.
rpm 25/01/2019
Loans
Keywords: Law; Account; Administrators